Neuro‐ophthalmology of invasive fungal sinusitis: 14 consecutive patients and a review of the literature. (24th January 2013) - Thurtell, Matthew J; Chiu, Alison LS; Goold, Lucy A; Akdal, Gulden; Crompton, John L; Ahmed, Rebekah; Madge, Simon N; Selva, Dinesh; Francis, Ian; Ghabrial, Raf; Ananda, Arj; Gibson, John; et al.
Abstract: Background: Invasive fungal sinusitis is a rare condition that usually occurs in immunocompromised patients and often presents as an orbital apex syndrome. It is frequently misdiagnosed on presentation and is almost always lethal without early treatment. Design: Retrospective case series of 14 consecutive patients with biopsy‐proven invasive fungal sinusitis from four tertiary hospitals. Participants: Fourteen patients (10 men and 4 women; age range 46–82 years). Methods: Retrospective chart review of all patients presenting with invasive fungal sinusitis between 1994 and 2010 at each hospital, with a close analysis of the tempo of the disease to identify any potential window of opportunity for treatment. Main Outcome Measures: Demographic data, background medical history (including predisposing factors), symptoms, signs, radiological findings, histopathological findings, treatment approach and subsequent clinical course were recorded and analysed. Results: Only one patient was correctly diagnosed at presentation. Only two patients were not diabetic or immunocompromised. The tempo was acute in two patients, subacute in nine patients and chronic in three patients. In the subacute and chronic cases, there was about 1 week of opportunity for treatment, from the time there was a complete orbital apex syndrome, and still a chance for saving the patient, to the time there was central nervous system invasion, which was invariably fatal. Only two patients survived – both had orbital exenteration, as well as antifungal drug treatment. Conclusions: Invasive fungal sinusitis can, rarely, occur in healthy individuals and should be suspected as a possible cause of a progressive orbital apex syndrome.